Thermodynamics - Honig, Jurgen M. (Academic Press, 1999)
This book provides a concise overview of thermodynamics, and is written in a manner which makes the difficult subject matter understandable. Thermodynamics is systematic in its presentation and covers many subjects that are generally not dealt with in competing books such as: Carathodory's approach to the Second Law, the general theory of phase transitions, the origin of phase diagrams, the treatment of matter subjected to a variety of external fields, and the subject of irreversible thermodynamics. The book provides a first-principles, postulational, self-contained description of physical and chemical processes. Designed both as a textbook and as a monograph, the book stresses the fundamental principles, the logical development of the subject matter, and the applications in a variety of disciplines. This revised edition is based on teaching experience in the classroom, and incorporates many exercises in varying degrees of sophistication. The stress laid on a didactic, logical presentation, and on the relation between theory and experiment should provide a reader with a more intuitive understanding of the basic principles. Graduate students and professional chemists in physical chemistry and inorganic chemistry, as well as graduate students and professionals in physics who wish to acquire a more sophisticated overview of thermodynamics and related subject matter will find this book extremely helpful. Key Features * Takes the reader through various steps to understanding: * Review of fundamentals * Development of subject matter * Applications in a variety of disciplines.